MEPIQUAT CHLORIDE AND SHADING EFFECTS ON SPECIFIC LEAF AREA AND K, P, CA, FE AND MN CONTENT OF LANTANA CAMARA L. - Matsoukis, Aristidis; Gasparatos, Dionisios; Chronopoulou-Sereli, Aikaterini (Emirates Journal of Food and Agriculture, 2015)
The effects of mepiquat chloride (MC) (0, 500 and 1000 mg l-1) on specific leaf area (SLA) and leaf potassium (K), phosphorus (P), calcium (Ca), iron (Fe) and manganese (Mn) content of Lantana camara L. plants were examined under 0% and 66% shading levels. All examined parameters and Fe were affected significantly by MC at 66% and 0% shading, respectively. MC decreased SLA of lantana compared to the control (0 mg l-1) irrespective of shading level with no significant differences in general. Increased SLA values were estimated with increased shading. K was increased significantly after spraying with MC at 1000 mg l-1, to a maximum, at 66% shading, compared to 0 mg l-1. P and Fe contents, in general, augmented as MC concentration increased. Mn remained stable with the increasing MC concentrations at 0% shading. On the other hand, Ca and Mn exhibited a significant peak after spray with MC concentration at 500 mg l-1, followed by a slight reduction, at the highest concentration, at 66% shading. K, P and Fe, in most cases, increased significantly, while Ca and Mn, in general, decreased, as shading increased. Our results could aid towards a fertilization program for lantana plants.